Thesaurus of investigation of professional fitness trainers' training in the higher educational institution - Василенко, Марина Миколаївна (ScienceRise: Pedagogical Education, 2016)
There were analyzed traditional pedagogical definitions: “specialist model”, “result of the study”, “readiness”, “professional training”. It was specified the meaning of notion “higher educational institution” as a separate type of institution that gives educational services at the certain level of higher education on choosen specialties taking into account the market demands and personal needs of student in intellectual, professional, cultural and ethical development, realizes educational, scientific, scientific-technical, upbringing, international, innovative and/or methodological activity. It was presented the essence of notion “fitness trainer” that is explained as specialist that gives in group and/or individual format the services on studying, teaching and/or elaboration of programs of application of physical exercises, stock and equipment for the different groups of population taking into accout their needs, connected with striving for optimal life quality that includes social, psychic, spiritual and physical components. There was considered professional training of the future fitness trainers in higher educational institutions as pedagogical system that provides integral totality of components, directed on formation in future specialists of professional competences and correspondent knowledge, skills and abilities within specialty “Physical culture and sport” (specialization “Fitness-trainer”), projected taking into account the requerements of consumers of educational services (employers) and society that allows after finish of educational program of certain level of higher education successfully carry out tasks and duties, specific for fitness trainer profession and also realize the own professional and personal development.